Dispositifs à variables inconnues - Emmanuel Grimaud (Ateliers d'Anthropologie)
Roleplay, speculative interaction scenarios, quirky machines, experimental platforms or experiment apparatuses can produce effects that reset a problem or question, even if (especially if) one does not control all of the variables. Rather than an anthropology for design, or an anthropology of design, or a design for anthropology (Murphy, 2016), this article offers a different path: at the boundaries of design, experimenting with a crowd of apparatuses whose variables are unknown, eluding the choice between a “rigid” or “wild” experiment design. In this context, AI and cinema are seen as two historical phases of a single plastic programme that began the day modernists decided that our eyes no longer sufficed, and that we needed to see through “an eye endowed with inhuman analytical properties” (Epstein). The aim is to understand the motives behind this strange unfinished programme, to situate ourselves in relation to it, to conduct its examination of conscience, to play with it rather than being its plaything, or to surpass it.